Estratégias de marketing em cooperativas - o caso da CESMA - Adams, Jaqueline (2006)
Most part of non-profit organizations, like co-operative associations, are not making use of the management science for a better development of their strategies. From a case study, this dissertation presents an analysis of the marketing strategies used by "Cooperativa dos Estudantes de Santa Maria - CESMA". To manage the research, the Marketing Mix 4 Ps Model was used- product, price, place (distributions) and promotion - what allowed to relate the co-operative association CUf rent strategies, to identify its weakest and strongest topics and the effectiveness and differences between the board' s practice and the needs of the associates. The results of the work indicate that the associates' needs lead to the acquisition of technology, such as computers, accessories and technical instruments (product), that the most important strategy is the lowest price practice (price), that the co-operative must optimize its order and delivery services, linking to the intemet (distribution) and that the communication channels are not satisfactory (promotion).